Gap-directed chemical lift-off lithographic nanoarchitectonics for arbitrary sub-micrometer patterning - Wang, Chang-Ming; Chan, Hong-Sheng; Liao, Chia-Li; Chang, Che-Wei; Liao, Wei-Ssu (Beilstein Journal of Nanotechnology, 2023)
We introduce a unique soft lithographic operation that exploits stamp roof collapse-induced gaps to selectively remove an alkanethiol self-assembled monolayer (SAM) on Au to generate surface patterns that are orders of magnitude smaller than structures on the original elastomer stamp. The smallest achieved feature dimension is 5 nm using a micrometer-scale structured stamp in a chemical lift-off lithography (CLL) process. Molecular patterns retained in the gaps between stamp features and their circumscribed or inscribed circles follow mathematical predictions, and their sizes can be tuned by altering the stamp structure dimensions, including height, pitch, and shape. These generated surface molecular patterns can function as biorecognition arrays or be transferred to the underneath Au layer for metallic structure creation. By combining CLL process with this gap phenomenon, soft material properties that are previously thought as demerits can be used to achieve sub-10 nm features in a straightforward sketch.
Keywords: chemical lift-off lithography; gap; self-assembled monolayer; sub-micrometer; surface patterning